Microbial Translocation in the Pathogenesis of HIV Infection and AIDS - Marchetti, Giulia (American Society for Microbiology, 2013)
In pathogenic simian immunodeficiency virus (SIV) and human immunodeficiency virus (HIV) infections, the translocation of microbial products from the gastrointestinal (GI) tract to portal and systemic circulation has been proposed as a major driver of the chronic immune activation that is associated with disease progression. Consistently, microbial translocation is not present in nonpathogenic SIV infections of natural host species. In vivo studies demonstrated that HIV/SIV-associated microbial translocation results from a series of immunopathological events occurring at the GI mucosa: (i) early and severe mucosal CD4(+) depletion, (ii) mucosal immune hyperactivation/persistent inflammation; (iii) damage to the integrity of the intestinal epithelium with enterocyte apoptosis and tight junction disruption; and (iv) subverted the gut microbiome, with a predominance of opportunistic bacteria. Direct in situ evidence of microbial translocation has been provided for SIV-infected rhesus macaques showing translocated microbial products in the intestinal lamina propria and distant sites. While the mechanisms by which microbial translocation causes immune activation remain controversial, a key pathogenic event appears to be innate immunity activation via Toll-like receptors and other pathogen recognition receptors. Accumulating clinical observations suggest that microbial translocation might affect HIV disease progression, response to therapy, and non-AIDS comorbidities. Given its detrimental effect on overall immunity, several interventions to prevent/block microbial translocation are currently under investigation as novel therapeutic agents for HIV/AIDS.